Exciency and Authority Chairman of the Corruption Eradication Commission for Bribery and Gratification Cases of the Governor of Papua According to Law Number 30 of 2002 Juncto Law Number 19 of 2019 Concerning the Corruption Eradication Commission - Mora Sangkot Hasibuan; Kusno Kusno; Toni Toni (Journal of Social Research, 2023)
This study aims to find out and analyze the existence of the KPK's position and authority based on law number 19 of 2019 concerning the Corruption Eradication Commission. As well as knowing and analyzing the actions of KPK Chairman Firli Bahuri in meeting the suspect in the bribery and gratuity case, the Governor of Papua, Lukas Enembe, violated the rules. This research is a type of normative research. So that it can be seen that the existence of the KPK in law enforcement in the field of corruption can be affected by the position of the KPK which is now a "state institution that is in the executive power cluster which in carrying out its duties and authorities is independent and free from the influence of any power". In addition, the state should not lose to corruptors. The state must be present in ensuring legal enforcement of corruptors who are detrimental to the state.